Implementation of the European mediacoach initiative in Portugal - Lapa, T.; Vieira, J.; Guerreiro, C.; Crespo, M.; Branco, S. (Media coach: How to become a media literacy coach, 2021)
This chapter illustrates the implementation of the training activities of the European MediaCoach Initiative in Portugal by the project’s national partner, the University Institute of Lisbon (ISCTE Instituto Universitario de Lisboa). The chapter begins with an introduction to media literacy in Portugal and highlights the European MediaCoach Initiative goals in Portugal. Furthermore, it describes the methods used to develop the MediaCoach training in Bulgaria, including the preparation, implementation and key factors that contributed to its success. The training programmes became more engaging by using an immersive approach through continuous learning and researching up-to-date information and news of digital literacy issues. The project offered seven courses and training, positively assessing and certifying 104 participants, but there were difficulties due to many dropouts in the training sessions. Overall, there was positive feedback on how the course challenged trainees to think outside the box and equipped them with knowledge and skills applicable to today’s technological society.